2022
DOI: 10.3389/fcvm.2022.1001982
|View full text |Cite|
|
Sign up to set email alerts
|

Artificial intelligence-assisted remote detection of ST-elevation myocardial infarction using a mini-12-lead electrocardiogram device in prehospital ambulance care

Abstract: ObjectiveTo implement an all-day online artificial intelligence (AI)-assisted detection of ST-elevation myocardial infarction (STEMI) by prehospital 12-lead electrocardiograms (ECGs) to facilitate patient triage for timely reperfusion therapy.MethodsThe proposed AI model combines a convolutional neural network and long short-term memory (CNN-LSTM) to predict STEMI on prehospital 12-lead ECGs obtained from mini-12-lead ECG devices equipped in ambulance vehicles in Central Taiwan. Emergency medical technicians (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…If they prove successful, it could significantly increase the efficiency of care delivery in the ICU. One-size-fits-all solutions are not effective in dealing with complex problems, as evidenced by the lack of improvement in septic shock outcomes in recent years despite various treatment guidelines (19,20) 22) reported using AI-assisted real-time analysis of electrocardiograms in the prehospital setting and found that it was feasible and had the potential to reduce delays in treatment times for patients requiring percutaneous coronary interventions (22). These examples demonstrate the use of AI for therapeutic guidance in medical decision-making for critically ill patients with good efficacy.…”
Section: Aid To Complex Decision-making In Critical Carementioning
confidence: 99%
See 2 more Smart Citations
“…If they prove successful, it could significantly increase the efficiency of care delivery in the ICU. One-size-fits-all solutions are not effective in dealing with complex problems, as evidenced by the lack of improvement in septic shock outcomes in recent years despite various treatment guidelines (19,20) 22) reported using AI-assisted real-time analysis of electrocardiograms in the prehospital setting and found that it was feasible and had the potential to reduce delays in treatment times for patients requiring percutaneous coronary interventions (22). These examples demonstrate the use of AI for therapeutic guidance in medical decision-making for critically ill patients with good efficacy.…”
Section: Aid To Complex Decision-making In Critical Carementioning
confidence: 99%
“…AI can also perform real-time electrocardiogram analysis to detect myocardial infarctions. A study by Chen et al ( 22 ) reported using AI-assisted real-time analysis of electrocardiograms in the prehospital setting and found that it was feasible and had the potential to reduce delays in treatment times for patients requiring percutaneous coronary interventions ( 22 ). These examples demonstrate the use of AI for therapeutic guidance in medical decision-making for critically ill patients with good efficacy.…”
Section: Applications Of Ai In Critical Care Patient Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…New software interpretation that utilizes machine learning may have entirely different sources of errors or be so accurate as to obviate the incremental gains from an approach such as this. 45,46…”
Section: Limitationsmentioning
confidence: 99%
“…New software interpretation that utilizes machine learning may have entirely different sources of errors or be so accurate as to obviate the incremental gains from an approach such as this. 45,46 Previous studies have used a variety of gold standards for true STEMI, including physician consensus of ECG findings, disposition to CCL, cardiac biomarkers, and CCL outcomes, which makes comparison difficult. The authors used appropriate CCL activation, determined based on a number of outcomes as well as cardiologist consensus.…”
Section: Limitationsmentioning
confidence: 99%